Insights for growth: Understanding the drivers of ASNAF entrepreneurial success in Malaysia - Hamid, Nadiah Abd; Ismail, Ida Suriya; Yunus, Nuridayu; Norizan, Saifulrizan; Palil, Mohd Rizal (Edelweiss Applied Science and Technology, 2024)
The aim of this study is to bridge a critical gap in the literature by exploring the factors that underpin the entrepreneurial success of ASNAF (ASNAF) individuals within the Malaysian context. ASNAF individuals, being eligible for zakat, represent a unique segment of entrepreneurs whose ventures intertwine Islamic finance principles, socio-economic challenges, and the pursuit of sustainable growth. Through a comprehensive empirical investigation, the purpose of this study is to provide nuanced insights into the specific drivers that contribute to the success of ASNAF-led enterprises and offer actionable recommendations for fostering inclusive entrepreneurship. This study used a quantitative survey involving 250 ASNAF entrepreneurs in Malaysia to capture their diverse experiences. By using factor analysis, five factors were subsequently identified as key drivers for entrepreneurs’ success. These factors are record-keeping, capital, employees, marketing strategy, and online business. The anticipated findings of this research include a nuanced understanding of the factors driving ASNAF entrepreneurial success, contributing to both academic knowledge and practical implications for policymakers, financial institutions, and the ASNAF community. This study aims to create an environment that supports long-term growth, social responsibility, and inclusive economic development among ASNAF people in Malaysia by shedding light on the untapped potential at the intersection of Islamic finance and entrepreneurship.